The non-stationary Arrow-Hurwich market - Panek, Emil (Economics and Business Review, 2003)
In the paper, basing on the Arrow-Hurwich market, an attempt is made to prove that non-stationary economic system is not a real obstacle in investigating of its stability. It is shown that the classical equilibrium is not condition sine qua non for stability of the market. (original abstract)